Diverse Frameworks on Retina Verification - Anitha, L; Arunvinodh, C (International Journal of Computer Sciences and Engineering, 2014)
This paper mainly presents different methods for the person authentication. The survey mainly includes the following methods; a high performance system with features obtained from human retinal images, retina verification using feature point based biometric pattern, then using the digital retinal images, retinal fundus biometric analysis, score level fusion of left and right irises, using 2-D matched filters, then using 2-D morlet wavelet method and finally using the biometric graph matching algorithm.